If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u = 30 + -2u Solving 3u = 30 + -2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '2u' to each side of the equation. 3u + 2u = 30 + -2u + 2u Combine like terms: 3u + 2u = 5u 5u = 30 + -2u + 2u Combine like terms: -2u + 2u = 0 5u = 30 + 0 5u = 30 Divide each side by '5'. u = 6 Simplifying u = 6
| X-(-10)=15 | | 3x+17=3(x+2)+11 | | x-3/10 | | 5x+3=2x-3+3x | | 7x+6=3x+8 | | 2x-5y=-45 | | -k-8(8k-6)=-16-k | | 1-4i= | | R-15=-12 | | 15500=C+0.30(15500) | | -2(-7W+3)-8W=2(W-5)-6 | | 2(x-7)=8+3x | | -1=k-9 | | x-3/10=4x | | -3c+7=-17 | | 7n+x=3x-n | | 6n+3=-4n+7 | | x²√25/289 | | 12x-3y=-36 | | (6x-4)(4n-5)= | | -78=3j+7-8j | | 25=40+s | | 27x=28 | | 4x^2+14-210=0 | | p-3/8 | | 3x/y=6 | | X+17=151 | | (12-5i)(7i+5)= | | A+2(y+3)=y+7 | | 6f-4+2f=20 | | 6x-8+15=-9 | | -6x-3x=5(x-5)-3(7x+1) |